737 Complex case of multiple sclerosis with multiple demyelinating locations (Balneo and PRM Research Journal, 2024)
Multiple sclerosis (MS) is a chronic inflammatory disorder with an unpredictable progression that affects the central nervous system and has significant emotional, social, and professional implications. The therapeutic approach is multifactorial and requires complex management coordinated by a specialized, multidisciplinary team over the long term. Current non-pharmacological treatment strategies under study, which may improve the course of the disease, focus on the gut microbiome and include the administration of probiotics and fecal transplantation. This study presents a case of secondary progressive multiple sclerosis in a young patient, with rapidly progressive evolution despite ongoing background therapy. The study analyzed literature data regarding both medical rehabilitation programs used in secondary progressive multiple sclerosis and other therapeutic strategies that can improve the quality of life. Medical rehabilitation has no proven impact on disease progression but can enhance the quality of life for patients with multiple sclerosis through spasticity management, improved mental health, increased mobility, and muscle strength. These therapeutic strategies can improve involvement in professional activities and participation in social and family life for patients with multiple sclerosis.